Dominant discourses at play: how children's soccer coaches of mixed-sex programs in Ontario, Canada, understand sex and gender - Hamer, J.; Giles, A. R. (International Sport Coaching Journal, 2024)
In this study, we explore how soccer coaches of children`s mixed-sex programs in Ontario understand sex and gender in the context of their coaching practices. Informed by feminist science studies and feminist methodologies, we conducted semistructured interviews with 11 coaches. Through critical discourse analysis, we identified the coaches` (re)production of three discourses: (a) gender is constructed but categorical; (b) inevitable and hierarchal sex differences necessitate sex segregation; and (c) girls` sport is vulnerable, and girls in sport require support. The results of this study indicate that these coaches` understandings of sex and gender are heavily informed by discourses of sex essentialism and sex and gender difference, which together legitimize the need for a binary sex/gender model of sport. Understanding the ways in which sport enforces and is shaped by the limited binary and naturalized notions of sex and gender is one step in reimagining a more just and inclusive model of sport, including children`s sport, and in creating sport spaces where players of all genders can thrive.